Association between APOL 1 Risk Genotypes and Left Ventricular Hypertrophy among Sub-Saharan Africans in Trypanosoma Brucei Gambiense Endemic Rural Area - Mupepe, Dominique M.; Buila, Nathan B.; Situakibanza, Hippolyte N.; Ekulu, Pp M.; Wameso, Marie-Noelle N.L.; Nkoy, Agathe B.; Nsimba , Exode S.; Bikoumou , Victoire A.; Karume, Kevin L.; Kayembe , Jean Marie N.; Heuvel , Lambertus P. Van den; Levtchenko , Elena N.; et al. (International Journal of Health, Medicine and Nursing Practice, 2024)
Purpose. The relationship between APOL1 variants and cardiovascular disease remains controversial, thus, this study assessed the association between APOL1 high-risk genotypes and left ventricular hypertrophy (LVH) among sub-Saharan African in T.b. gambiense endemic area. Methodology. We enrolled 238 subjects living in the region of Masimanimba, an endemic area of T.b.gambiense HAT. We evaluated the association between LVH on echocardiography and the status of APOL1 genes in participants with or without HAT. APOL1 high-risk genotype (HRG) was defined as the presence of two risk variants (G1/G1, G2/G2, or G1/G2), and a low-risk genotype (LRG) with the presence of 0 or 1 single variant. Student's and Pearson's Chi2 tests or Fisher's exact test were used to compare means and proportions. The Wilcoxon/Mann-Whitney test was used to compare medians. A multivariate logistic regression model was used to identify independent determinants of LVH. Odds ratios were provided with their 95% confidence intervals (Cis). Statistical significance was set at p < 0.05, based on 2-tailed test. Findings. The prevalence of LVH (31.5%) increased with age and was similar in HAT-infected and non-infected subjects (29.8% vs. 32.6%; p=0.376). The trend of a greater left ventricular mass in participants with LVH carrying APOL1 HRG compared to those with LRG was not statistically significant (141g/m2 vs. 125 g/m2; p = 0.253). The frequency of HRG among participants with LVH was similar between HAT-infected and non-infected (15.8% vs. 9.1%; p = 0.806). Age â‰¥ 38 years [OR 2.5 (95% CI: 1.4-4.5), p = 0.001], hypertension [OR 2.4 (95% CI: 1.1-5.3), p = 0.034], WHR > 0.5 [OR 2.0 (95% CI: 1.0-3.6), p = 0.018] and CKD [OR 1.7 (95% CI: 1.0-3.0), p = 0.049] were associated with LVH. In multivariable logistic regression analysis age â‰¥ 38 years was the only independent determinant of LVH [ORa 2.0 (95% CI: 1.1-3.8), p = 0.020]. Unique contribution to theory, practice and policy. An assessment of cardiovascular risk is essential for individuals with LVH carrying APOL1 HRG in order to benefit from early and appropriate medical intervention. Further larger prospective follow-up survey is required to assess the incidence of LVH in individuals with APOL1 HRG variants.